2002
DOI: 10.1128/jcm.40.9.3198-3203.2002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Rapid, Automated Ribotyping and DNA Macrorestriction Analysis of Burkholderia pseudomallei

Abstract: An automated ribotyping device (RiboPrinter) was used to determine the ribotypes of a collection of Burkholderia pseudomallei isolates. In a preliminary evaluation with the restriction enzymes BamHI and EcoRI, the protocol with EcoRI was more discriminating. The reproducibilities of the ribotypes obtained with EcoRI (EcoRI ribotypes) were determined by testing three levels of bacterial loads. The performance of the manufacturer's software was assessed by comparing the machine-optimized ribotypes with the type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 16 publications
(15 reference statements)
0
25
0
Order By: Relevance
“…There was no significant difference between the rest of the groups (p=0.69) (Figure 4). Further analysis revealed that two pairs of strains from the Northern Territory clinical group were indistinguishable, while the remaining 7 were classified as distinct by DNA macro restriction with Xbal (Inglis et al, 2002). There was no significant difference in chlorine tolerance between soil and water environmental isolates from Western Australia; a result that was anticipated since most of these isolates were from a single cluster and had a high homology by PFGE.…”
Section: Survival Of Bacteria In Chlorinementioning
confidence: 89%
“…There was no significant difference between the rest of the groups (p=0.69) (Figure 4). Further analysis revealed that two pairs of strains from the Northern Territory clinical group were indistinguishable, while the remaining 7 were classified as distinct by DNA macro restriction with Xbal (Inglis et al, 2002). There was no significant difference in chlorine tolerance between soil and water environmental isolates from Western Australia; a result that was anticipated since most of these isolates were from a single cluster and had a high homology by PFGE.…”
Section: Survival Of Bacteria In Chlorinementioning
confidence: 89%
“…A second, complementary genotyping method was introduced that used an automated ribotyping platform, and the two methods were compared. 8 The addition of genotype analytical software (Bionumerics, Kortrijk, Belgium) allowed for the assembly of a genotype archive based on the clinical and environmental isolates steadily amassing in the WA culture collection. As other PCRbased genotyping methods were introduced, the question arose as to which method should serve as the first-line genotyping system and what should be the definitive typing method.…”
Section: Introductionmentioning
confidence: 99%
“…This protocol enabled assembly of a collection of B. pseudomallei and other Burkholderia species, benchmarked against type culture collection strains and imported B. pseudomallei strains from other research centres. Our Burkholderia Culture Collection has been genotyped by EcoR1 ribotyping and Xba1 DNA macrorestriction analysis 5 . The increasing genetic complexity of the genus Burkholderia made us doubt the wisdom of relying on a single PCR product to confirm the identity of new clinical isolates of B. pseudomallei.…”
Section: Introductionmentioning
confidence: 99%